2009
DOI: 10.2202/1932-0191.1037
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Anticipating Anxiety-Related Symptoms: An Investigation of Paradoxical-Success Imagery in the Laboratory

Abstract: This study investigated the efficacy of a paradoxical imagery strategy that consisted of participants imaging themselves experiencing symptoms characteristic of competitive anxiety, prior to executing a golf-chip shot. Forty male golfers of moderate skill level participated in a twoday experiment conducted in the laboratory. Wegner's (1994) theory of ironic processes of mental control served as the theoretical framework. In addition to the paradoxical component, the imagery technique (paradoxical-success image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 61 publications
(139 reference statements)
0
5
1
1
Order By: Relevance
“…Graham Jones, Sheldon Hanton, and colleagues have asserted in a number of papers and studies that it is more advantageous for athletes to focus efforts towards reframing the interpretation of anxiety symptoms from a debilitative to a facilitative perspective as opposed to learning techniques designed to reduce anxiety (e.g., Hanton & Jones, 1999a;Hanton & Jones, 1999b;Jones, 1995;Jones, Hanton, & Connaughton, 2002;Jones, Hanton, & Connaughton, 2007;Jones, Hanton, & Swain, 1994;Jones, Swain, & Hardy, 1993;Mellalieu, Hanton, & Thomas, 2009;Thomas, Maynard, & Hanton, 2007). A number of applied studies utilizing imagery within mentalskills training packages have offered support for their argument (e.g., de la Peña, 2009;Hanton & Jones, 1999b;Mamassis & Doganis, 2004;Mellalieu et al, 2009;Thomas et al, 2007). However, the imagery scripts implemented among these studies have varied.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Graham Jones, Sheldon Hanton, and colleagues have asserted in a number of papers and studies that it is more advantageous for athletes to focus efforts towards reframing the interpretation of anxiety symptoms from a debilitative to a facilitative perspective as opposed to learning techniques designed to reduce anxiety (e.g., Hanton & Jones, 1999a;Hanton & Jones, 1999b;Jones, 1995;Jones, Hanton, & Connaughton, 2002;Jones, Hanton, & Connaughton, 2007;Jones, Hanton, & Swain, 1994;Jones, Swain, & Hardy, 1993;Mellalieu, Hanton, & Thomas, 2009;Thomas, Maynard, & Hanton, 2007). A number of applied studies utilizing imagery within mentalskills training packages have offered support for their argument (e.g., de la Peña, 2009;Hanton & Jones, 1999b;Mamassis & Doganis, 2004;Mellalieu et al, 2009;Thomas et al, 2007). However, the imagery scripts implemented among these studies have varied.…”
mentioning
confidence: 99%
“…More recently, de la Peña (2009) and Mellalieu et al (2009) demonstrated the benefits of including anxiety-related symptoms (i.e., motivational general-arousal imagery, Martin et al, 1999) within the imagery scripts. For example, de la Peña (2009) demonstrated that golfers, who imaged themselves performing effectively and confidently with symptoms characteristic of competitive anxiety, were able to improve performance in a golf-chipping task conducted in the laboratory during both competitive and pressure situations. In a study conducted in the field, Mellalieu et al (2009) trained five rugby players to regularly image successful performance during important games with concurrent anxiety-related symptoms present.…”
mentioning
confidence: 99%
See 3 more Smart Citations